2004
DOI: 10.1002/chem.200305567
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrolled Release and Uptake of a Porphyrin Guest by Dithienylethene‐Tethered β‐Cyclodextrin Host Dimers

Abstract: Two photoswitchable dithienylethene‐tethered β‐cyclodextrin dimers were synthesized to function as host molecules with an externally controllable binding affinity. The cyclodextrin cavities of these dimers are linked through their secondary sides by a photochromic dithienylethene unit that is connected to the secondary rim either directly (4) or through propyl spacers (9). Irradiation with light switches these dimers between a relatively flexible (open) and a rigid (closed) form. The binding properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…plexes with different binding stoichiometries, the smaller TSPP forming a 1:1 complex with 1 and the larger TBPyP being bound by two CD dimers 1. This is in accordance with previous complexation studies of CD dimers with TSPP [16,17,19] and TBPyP. [16] It is well known that TSPP, because of its small size, can only accommodate two CD cavities (i.e., one CD dimer).…”
Section: Complexation Studiessupporting
confidence: 89%
See 2 more Smart Citations
“…plexes with different binding stoichiometries, the smaller TSPP forming a 1:1 complex with 1 and the larger TBPyP being bound by two CD dimers 1. This is in accordance with previous complexation studies of CD dimers with TSPP [16,17,19] and TBPyP. [16] It is well known that TSPP, because of its small size, can only accommodate two CD cavities (i.e., one CD dimer).…”
Section: Complexation Studiessupporting
confidence: 89%
“…Such significant differences in binding can be sufficient to achieve substantial release of guest molecules from the CD dimer upon metal chelation. [17] Calorimetry was shown to be a powerful tool for the elucidation of the complexation thermodynamics, as it allows interpretation of the influence of metal chelation and charges upon the binding properties of the EDTA-tethered CD dimers. Attribution of the separate contributions of electrostatic and hydrophobic interactions is readily achieved for interactions in which one of the two is systematically changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that 23a binds porphyrin 16a more strongly than 23b does. This binding difference of 23 allows the photocontrolled reversible release and uptake of porphyrin 16a in solution [46] …”
Section: Covalently Linked CD Dimers Including Guest Moleculesmentioning
confidence: 99%
“…It is possible that porphyrins are applied as guest molecules for special purposes. For example, a supramolecular system composed of photoswitchable -cyclodextrin dimmers (host) and tetrakis-sulfonatophenyl porphyrin (guest) is a good candidate for using as photocontrollable (drug) delivery systems and might find application in, for example, photodynamic cancer therapy [92]. Besides, porphyrin nanostructures are attractive building blocks because of their electronic, optical, and catalytic properties [93][94][95].…”
Section: Porphyrinsmentioning
confidence: 99%